Antimicrobial Activity and Physical Characteristics of Oil Extracted from Alligator Pepper Seed (Aframomum melegueta) Cultivated in Owo, Ondo State, Nigeria - Gbenga, Aladekoyi; Shakpo, Itunnu Olubunmi (Biological Sciences - PJSIR, 2014)